Estrutura e dinâmica da abundância de bactérias, protozoários flagelados e ciliados planctônicos : respostas ao cultivo de peixes em tanques-rede. - Pereira, Danielle Goeldner (2008)
The present study evaluated the effect of waste from fish culture in net cages on the abundance of heterotrophic fraction of microbial planktonic community (bacteria, flagellates and ciliates), in an arm of Rosana reservoir, Paranapanema river (Brazil). We have tested the hypothesis that high values and a consecutive abundance increase, in time, would be observed at downstream region of installed cages. The present experiment was performed during 120 days at 100 and 400 m up and 100 and 400 m down the tanks. Spatial and temporal significant differences of abundance values were registered. However, a general tendency of similar values between the regions analyzed, the lack of a gradate increase of the values a long the time and the predominance of top-down control on the communities structure, suggest that the waste by aquiculture did not lead to a deviation of spatial and temporal nature patterns on abundance of heterotrophic fraction of microbial planktonic community, in the studied area. The lack of alterations associated to aquiculture was attributed to the ambient type, hydrodynamic, degree of isolation and the number of cage culture used.